Abstracts 2019
DOI: 10.1136/bmjopen-2019-ems.29
|View full text |Cite
|
Sign up to set email alerts
|

29 Feasibility of using a defibrillator to provide real-time and post-event feedback to paramedics on the quality of their CPR

Abstract: professionals due to different barriers. This study aims at reviewing if the use of pharmacological methods for pain provided during the emergency care of pediatric trauma patients is proper. Method Retrospective study of 560 consecutive clinical records of trauma patients, aged from 0 to 18, assisted from March to December 2017 by Advanced Life Support Units. Minor injuries excluded. Results Median age was 12 years (IQR 8-15). 71.8% ( 402) males. The most common diagnoses were upper limbs fractures and disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Further studies should now be carried out to assess the most effective way of maintaining an adequate compression depth. These studies could consider two different approaches: forcing participants to deliver compressions from the patient’s side [ 65 ], using a feedback device [ 66 , 67 , 68 , 69 ] or both together.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should now be carried out to assess the most effective way of maintaining an adequate compression depth. These studies could consider two different approaches: forcing participants to deliver compressions from the patient’s side [ 65 ], using a feedback device [ 66 , 67 , 68 , 69 ] or both together.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the feedback can be audio such as, "Compress deeper" and "Compress Faster". Multiple studies have confirmed that these devices help inexperienced bystanders and even medical professionals to perform better CPR than without these devices 103,104,105,106,107,20 .…”
Section: Video-assisted Cprmentioning
confidence: 99%